Ontogenesis of anselmian speculative thought - Corti, Enrique Camilo (Anales del Seminario de Historia de la Filosofía, 2019)
De concordia, the last treaty written by Anselmo constitutes a privileged high point in the ontogenetic process of his thought. I will try to outline the overall structural aspects of this text that I consider important to define its belonging to this ontogenic process:a) This work is inscribed —together with Monologio and Cur deus homo— in the process of construction of the anselmian speculative thought;b) The spectulative aspect is closely associated to language through the «nihil» notion;c) The articulation between freedom and necessity in M, and the unfolding of the centre of DC (in the textual centre and the objective centre) are both subsidiary to said aspect.
Keywords: speculative thougt; ontogenesis; freedom; necessity; structure; hermeneutics